The relationship between interpersonal emotional regulation and psychological resilience in nursing undergraduates: a cross-sectional study and network analysis - Huai, Panpan; Liu, Panyu; Wang, Xiaomeng; Wang, Yunan; Yang, Hui; Yan, Meiqin; Guo, Jinli (Frontiers in Psychology, 2025)
Background and purposeNursing students are more likely to have mental health problems due to the influence of many social environment factors, such as busy professional courses, difficult balance of learning and practice and complex and changeable clinical work environment. Psychological resilience, as a well-known protective factor, plays an important role in maintaining students’ mental health. At the same time, from the perspective of social interaction, the particularity of close interpersonal contact (including colleague relationship, nurse–patient relationship, etc.) in clinical practice makes interpersonal emotion regulation ability of nursing students have great significance. The emotion-regulation framework suggests a strong link between psychological resilience and emotional regulation. However, the correlation and function between the various components of psychological resilience and interpersonal emotional regulation are still unclear. Network analysis can realize the objective analysis and prediction of complex symptoms. This study investigated the network structure of interpersonal emotional regulation ability and psychological resilience in nursing undergraduates, aiming to identify central and bridge nodes and provide suggestions for precise intervention of interpersonal emotional regulation ability and psychological resilience in nursing undergraduates.MethodsA total of 1,948 nursing undergraduates were included in our study. Interpersonal Regulation Questionnaire (IRQ) was used to assess interpersonal emotional regulation. Psychological Resilience levels were assessed using The Connor-Davidson Resilience Scale (CD-RISC). Network analysis is used for statistical analysis.ResultsNetwork analysis revealed that IRQ14 (Enjoy being with friends), IRQ11 (Like to share), and CD-RISC11 (Believe in achieving goals) are core nodes of the interpersonal Emotional regulation-psychological resilience network. IRQ14 (Enjoy being with friends), CD-RISC2 (intimate relationship), and CD-RISC3 (The help of fate) are bridging nodes linking interpersonal emotional regulation and psychological resilience. In addition, the network structure is slightly different between different grades (upper and lower grades).ConclusionThe relationship between core nodes and bridge nodes revealed in this study (including interpersonal relationship, positive emotion, optimistic personality and self-efficacy, etc.) may provide help for the accurate intervention of students’ interpersonal emotion regulation ability and psychological resilience level.